DYNAMICS OF CHANGES IN BIOMETRIC INDICATORS OF SUNFLOWER PLANTS DEPENDING ON BASIC TILLAGE METHODS AND GROWTH REGULATOR IN THE SOUTHERN STEPPE OF UKRAINE - Yeremenko, O.; Onyshchenko О. (Scientific Progress & Innovations, 2020)
Sunflower cultivation and sunflower oil production occupies a leading position and reaches about 95% of the total volume of vegetable oils in Ukraine. The article presents the results of researching Colombi and Talento high oil-yielding hybrids of Syngenta company under different tillage and application of AKM-K1 and AKM-K2 plant growth regulators in different combinations in the conditions of insufficient moistening of the southern Steppe of Ukraine. The experiments were conducted in2017–2019 in the fields of “Energy-2000” LLC in Melitopol district of Zaporizhzhia region. The soils of the enterprise are clay loam southern black soils. The research years differed by the amount of precipitation, but they all were characterized by severe drought at different stages of sunflower plants’ growth and development. AKM-K1 plant growth regu-lator (PGR) was used for pre-sowing treatment of sunflower seeds, and AKM-K2 PGR – for vegetating plants. Plants’ sampling was conducted in accordance with the BBCH scale and generally accepted research methods. No significant difference was observed between the hybrids in the number of leaves per plant. In the variant AKM-K1 + AKM-K2 on the plants of Talento hybrid at deep loosening, the plants had the maxi-mum height (172.9 cm) according to 2019 data. The same year, the plants of Colombi hybrid formed the maximum stem diameter (2.93 cm) in the variant of AKM-K1 + AKM-K2 with deep loosening. In 2018, which was the most arid among the studied years, the effect of AKM-K1 and AKM-K2 growth regulators was the maximum. This can be confirmed by the increase in linear size: the plants of Colombi hybrid at deep loosening had increased indices by 9.7 to 22.7 %, and at plowing – from 8.0 to 23.0 %. For sunflower plants of Talento hybrid, the results were recorded from 8.1 to 26.5 % increase at deep loosening, and from 6.7 to 26.2 % at plowing. It was established that hydrothermal conditions of the year had the greatest effect on the formation of biometric parameters of Colombi and Talento sunflower hybrids. The correlation coefficient between the amount of precipitation and stem diameter is equal to r=0.806, and between the amount of pre-cipitation and plant height reaches the value of r=0.956.Thus, we propose to use anti-stress technologies for growing high yields of sunflower under the effect of AKM-K1 and AKM-K2 plant growth regulators and to conduct deep loosening to preserve productive moisture in the soil.